A high school guidance programme aimed at the primary prevention of sexual abuse of children as part of a national strategy for the prevention of child sexual abuse in South Africa - McGregor, Dale (Rhodes University, Faculty of Education, Department of Education, 1994)
The sexual abuse of children has become recognised as a major problem affecting children in most, if not all, countries of the world. The prevention of such abuse has, in the last decade, become an issue of international significance. In South Africa, prevention efforts are mainly informal ad hoc strategies initiated by individuals or organisations. As such they suffer from being short-lived and often isolated. Prevention efforts fall into the general categories of primary, secondary and tertiary prevention. Primary prevention focuses on preventing abuse from occurring at all. There are two main aspects to this type of prevention. The first aims at teaching children to protect themselves. The second aims at preventing the development of a disposition to abuse. This study set out to suggest and justify the adoption of a national strategy appropriate to the South African situation, including an overview of what can be done through the schooling system. This strategy will provide a framework and context for individual efforts, and hopefully stimulate new programmes. In addition, a detailed prevention programme for implementation in the secondary school, through the medium of the subject Guidance, was developed. This programme addressed itself mainly to that primary aspect of prevention concerned with preventing people from developing a disposition to abuse. The programme consists of lesson plans, teacher's notes and worksheet materials for pupils.
Keywords: Child abuse -- South Africa -- Prevention; Educational counseling -- Keiskammahoek; Educational counseling -- South Africa